Penamaan Desa di Kecamatan Tapung Kabupaten Kampar - Della Putri Andini; Melia Anggraeni; Ramaida Ramaida; Siti Samsiah (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Naming is a symbol process that refers to a referent. Giving a name to each area is not only for designation but to make it easier for someone to recognize the identity of the area. Each area is given a name by the community based on the situation and condition of each area. This study uses etymological and semantic approaches. This study describes: 1) the origin of village naming in Tapung District, Kampar Regency "based on natural elements", namely because of natural phenomena, which are used as special places 2) the origin of village nomenclature "based on circumstances and expectations" , such as real environmental conditions or have higher potential for the local people 3) the origin of the nomenclature of villages and hamlets "based on the process of establishment", is to identify the origin in determining the description of the name of the village. The results of the study show that the names of villages in Tapung sub-district are in the form of nouns, adjectives, and a small part are in the form of numerals. The majority of village names in Tapung District are based on natural elements, only a few are based on circumstances and expectations, as well as the process of their establishment.